ICT in special education - Chaidi, Irene; Drigas, Athanasios; Karagiannidis , Charalampos (Technium Social Sciences Journal, 2021)
In recent years, worldwide and in our country, the view has been established that all students, regardless of any element of differentiation, special need or characteristic related to national, cultural or social identity, should have equal learning opportunities in one school for all. The use of Information and Communication Technologies (ICT) contributes significantly to the learning process. Especially for students with special educational needs, ICT provides rich educational experiences. The following work refers to ICT in the field of application of Special Education, in assistive technology, educational sortware, which provides opportunities to approach knowledge, socialization of individuals and removal of physical barriers to access to knowledge of students with special educational needs .